Human Resource Development in Transport in the Context of Contemporary Socio-Economic and Technological Changes – Challenges to the Education and Training System - Atanassova, Margarita (Research Papers, 2021)
The competencies of employees in the transport sector are a significant factor in increasing the efficiency of rail, road, air and water transport. The successful development of human resources in the sector requires providers of education and training in the field of transport to be thoroughly aware of the changes in work processes. In the context of the modern dynamics of technologies, business scenarios and services offered in the transport sector, the article systematizes the main challenges for the education and training system in the field of transport with emphasis on the role of higher education as a provider of formal education (bachelor’s, master’s anddoctoral programs) and non-formal training